Ramadan Fasting and Patients with Cancer: State-of-the-Art and Future Prospects - Bragazzi, Nicola Luigi; Briki, Walid; Khabbache, Hicham; Rammouz, Ismail; Chamari, Karim; Demaj, Taned; Re, Tania Simona; Zouhir, Mohamed (Frontiers in Oncology, 2016)
Ramadan fasting represents one of the five pillars of the Islam creed. Even though some subjects (among which patients) are exempted from observing this religious duty, they may be eager to share this particular moment of the year with their family and peers. However, there are no guidelines or standardized protocols that can help physicians to properly address the issue of patients with cancer fasting in Ramadan and correctly advising them. Moreover, in a more interconnected and globalized society, in which more and more Muslim patients live in the Western countries, this topic is of high interest also for the general practitioner. For this purpose, we carried out a systematic review on the subject. Our main findings are that (1) very few studies have been carried out, addressing this issue, (2) evidence concerning quality of life and compliance to treatment is contrasting and scarce, and (3) generally speaking, few patients ask their physicians whether they can safely fast or not. For these reasons, further research should be performed, given the relevance and importance of this topic.